Nanomaterial Interfaces in Biology Methods and Protocols - Bergese, Paolo; Hamad-Schifferli, Kimberly; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The intersection of nanotechnology with biology has given rise to numerous ideas for new ways to use nanotechnology for biological applications. Nanomaterials possess unique size- and material-dependent properties which make them attractive for improving regular biomedical fields, such as drug delivery, imaging, therapy, and diagnostics. Divided into three convenient sections, Nanomaterial Interfaces in Biology: Methods and Protocols covers protocols describing synthesis, fabrication, and construction of bio-nanomaterial interfaces, characterization protocols of bio-nanomaterial interfaces, and applications which utilize the bio-nanomaterial interfaces. Written in the highly successful Methods in Molecular Biology series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible Nanomaterial Interfaces in Biology: Methods and Protocols will serve the new and emerging scientific community, enabling new capabilities and technologies that were not previously possible in medicine and biology.
Preparation of 2 nm Gold Nanoparticles for In vitro and In vivo Applications -- DNA Conjugation to Nanoparticles -- Conjugation of Nanoparticles to Proteins -- Water-Solubilization and Functionalization of Semiconductor Quantum Dots -- Synthesizing and Modifying Peptides for Chemoselective Ligation and Assembly into Quantum Dot-Peptide Bioconjugates -- Reliable Methods for Silica Coating of Au Nanoparticles -- Surface Modifications by Polymers for Biomolecule Conjugation -- Functionalization Protocols of Silicon Micro-Nano-Mechanical Biosensors -- Stability and Aggregation Assays of Nanoparticles in Biological Media -- Electrochemical Measurements of DNA Melting on Surfaces -- Formation and Characterization of Nanoparticle-Protein Corona -- Electrophoretic Implementation of the Solution-Depletion Method for Measuring Protein Absorption, Adsorption Kinetics, and Adsorption Competition Among Multiple Proteins in Solution -- Hyperspectral Microscopy for Characterization of Gold Nanoparticles in Biological Media and Cells for Toxicity Assessment -- Immunochemistry, Electron Tomography and Energy Dispersive X-Ray Spectroscopy (EDXS) on Cryosections of Human Cancer Cells Doped with Stimuli Responsive Polymeric Nanogels Loaded with Iron Oxide Nanoparticles -- Zwitterion Siloxane to Passivate Silica Against Non-Specific Protein Adsorption -- Preparation and Characterization of DNA Block Copolymer Assemblies Loaded with Nanoparticles -- Polyaspartic Acid Coated Iron Oxide Nanoprobes for PET/MRI Imaging -- Ligand Synthesis and Passivation for Silver and Large Gold Nanoparticles for Single-Particle-Based Sensing and Spectroscopy -- Non-Covalent Intracellular Drug Delivery of Hydrophobic Drugs on Au NPs -- Modification of Carbon Nanotubes for Gene Delivery Vectors -- Lipid-Based Nanoparticles as Non-Viral Gene Delivery Vectors -- Stabilizing Gold Nanoparticle Bioconjugates in Physiological Conditions by PEGylation.
Keywords: Biotechnology; Nanotechnology; Biotechnology; Nanotechnology